Nature of science in students' discussions on disagreement between scientists following a narrative about health effects of the Fukushima Daiichi accident. Issue 1 (2nd January 2023) - Hamza, Karim; Wojcik, Andrzej; Arvanitis, Leena; Haglund, Karin; Lundegård, Iann; Schenk, Linda
ABSTRACT: We explored the potential for addressing nature of science through a historic narrative about disagreement between researchers concerning a socio-scientific issue, incidence of juvenile thyroid cancer following the Fukushima Daiichi nuclear accident. The narrative was developed from authentic sources and tested in two cycles. Eight groups of three to four high-school students were audio recorded. Transcripts were analyzed regarding what nature of science emerged in the discussions and what understanding about NOS could be discerned, using three complementary NOS-frameworks (Consensus-NOS, Whole Science-NOS, FRA-NOS). Together, the student groups touched upon 19 different NOS-themes as they tried to make sense of the disagreement related in the narrative. All groups addressed a common core of NOS-themes, most of which were central to the narrative itself, although some themes that were not part of the narrative also emerged. Students displayed a basic understanding of the tentative, empirical, and subjective nature of science together with the role of evidential relevance and completeness of evidence related to the choice of scientific methods. On the other hand, students did not reckon with peer review as a means for establishing knowledge and resolving disagreement. Moreover, although students readily accepted disagreement as a basic property of science, they had difficulty handling this disagreement when coping with the SSI in the narrative. We discuss how the combination of history of science-in-the-making and SSI in narrative form offers opportunities to teach NOS without risking simplified messages of how scientific knowledge develops or how science can be used to address socio-scientific issues.